INFECTION PREVENTION AND CONTROL IN PRIMARY HEALTH CENTERS: A MIXED-METHOD STUDY OF NIGERIAN HEALTH WORKERS IN SOUTHWEST NIGERIA STATE - Adetumi Adetunji Subulade; Adejoke Esther Ogundana; Olumuyiwa Peter Oluyide; Abiola Tolulope Subulade (Journal of Public Health Research and Community Health Development, 2026)
Background: The World Health Organization warned in its report that infections were emerging at a rate never seen before, and with increase in world travel the potential for emerging infections to spread rapidly and the cause of global epidemics is a major concern. Health workers have become victims of infectious diseases, where infection prevention and control (IPC) practices are not adequate. Purpose: This study assessed and compared IPC practices in rural and urban primary health centers (PHCs) in a south-west state in Nigeria. Methods: The study was a comparative cross-sectional study design using mixed method. Self-administered questionnaires and key-informant interview approaches were used for data collection among health workers in the PHCs in Ekiti State, Nigeria. The data was analyzed using SPSS version 27. Results: More health workers in the rural PHCs (96.4%) had work experience over 5 years (p=0.001) and 98.1% of those in urban PHCs with the work experience had good knowledge of IPC (p=0.027). Training on IPC was significantly associated with positive attitude in the urban (p=0.044). Work experience showed relationship with the IPC practice in the rural (p=0.000) while the knowledge showed relationships in both rural and urban PHCs. Work experience was a predictor of IPC practices in the rural (AOR=2.157, 95%, CI=1.014–9.786) and knowledge was a predictor in both rural (AOR=4.927, 95%, CI=1.453–24.524) and urban PHCs (AOR=3.273, 95%, CI=1.824–5.729). Conclusion: The health workers had good practice of IPC across the urban and rural PHCs with knowledge as a predictor.